International remittance rails as infrastructures: embeddedness, innovation and financial access in developing economies. Issue 5 (3rd September 2019) - Rodima-Taylor, Daivi; Grimes, William W.
Abstract: Remittances to developing economies constitute one of their most important and consistent forms of capital inflow, but have long been limited by costs and risks associated with trans-border payments. New digital platforms lower these, with significant implications for financial inclusion and economic development. Constituting an important element of developing countries' engagement with international finance, remittances engender new opportunities for empowerment and vulnerability. This article analyzes recent developments in international remittances to developing countries through the lens of infrastructure. The infrastructural perspective reveals important junction points between diverse money transfer pathways and institutions, depicting their spatial configuration and relationality as well as their potential to affect power differentials, and allowing for a socially embedded view of digital disruption. Drawing on examples in Africa and Asia, we show that the new generation of remittance infrastructures are best understood as assemblages of multiple elements, conjoining monopolistic trunks that depend on local innovations to traverse the 'last mile' to reach end-users. The vibrancy and indispensability of local networks and innovation, along with competition among core platforms, allow for significant agency and economic opportunity even among communities beset by poverty.